2019
DOI: 10.21273/hortsci13567-18
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Growth, Nitrogen Nutrition, and Yield of Hydroponic Lettuce

Abstract: The effect of different nitrogen (N) concentrations on growth changes, leaf N concentration and accumulation patterns, N nutrition index (NNI), fresh weight yield, and N use efficiency (NUE) was determined for lettuce grown over three consecutive seasons (fall, winter, and spring) in a recirculating hydroponic system, under unheated and naturally lit hoop house in Uvalde, TX. The lettuce cultivars Buttercrunch, Dragoon, and Sparx were grown at six N concentrations, initially 100, 150, 200, 250, 300, and 400 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Generally, an excessive nitrogen supply is usually accompanied by low nitrogen use efficiency [ 36 , 37 ]. As shown in Table 3 , the nitrate use efficiency for new C input derived from the CO 2 assimilation (as indicated by the C C /N N ratio) was the lowest for Bn plantlets when the nitrate concentration increased to 40 mM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, an excessive nitrogen supply is usually accompanied by low nitrogen use efficiency [ 36 , 37 ]. As shown in Table 3 , the nitrate use efficiency for new C input derived from the CO 2 assimilation (as indicated by the C C /N N ratio) was the lowest for Bn plantlets when the nitrate concentration increased to 40 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the nitrate/ammonium use efficiency for new C input derived from CO 2 assimilation/sucrose utilization can be represented by the corresponding C/N ratio for Bn plantlets [9]. Generally, an excessive nitrogen supply is usually accompanied by low nitrogen use efficiency [36,37]. As shown in Table 3, the nitrate use efficiency for new C input derived from the CO 2 assimilation (as indicated by the C C /N N ratio) was the lowest for Bn plantlets when the nitrate concentration increased to 40 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Where data exists regarding CEA systems, it is usually highly bespoke to the system design and conditions of the experiment, thus direct comparisons are difficult to make. Studies carried out on salad crops in CEA systems have shown a wide range of N‐NUEs, covering two orders of magnitude (2%–104%) (e.g., Consentino et al, 2022; Djidonou & Leskovar, 2019; Pennisi et al, 2019; Santamaria et al, 2002; Yang & Kim, 2020; Wang et al, 2021) (Table 4). Data are more difficult to find for other elements to make comparisons, which are poorly represented in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, others have shown that phytotoxicity reduces height and biomass production of hydroponic lettuce (Hoque et al, 2007). Further, according to Djidonou and Leskovar (2019), nutrient requirements of lettuce can be cultivar specific. This could explain the fact that leaf area and shoot FW of 'Monte Carlo' were not negatively affected by SE-2.…”
Section: Leaf Area (Cmmentioning
confidence: 98%